AUDIENCE ENCODING-DECODING ANALYSIS IN TIKTOK’S DARK ROMANCE CONTENT - Fathimah, Anisah Nur (Universitas Negeri Surabaya, 2025)
This study analyzes how audiences respond to violent portrayals in dark romance content on TikTok using Stuart Hall’s (1980) encoding-decoding theory as the main framework. Audience reactions are categorized into three positions: dominant-hegemonic, negotiated, and oppositional. The data consists of five selected TikTok posts under the hashtag #darkromance, with the three most-liked comments from each post (fifteen in total) examined through qualitative content analysis. The focus of the analysis is on textual elements such as captions, hashtags, and written comments, supported by visual cues when relevant. The findings reveal that audience responses vary depending on how the content is framed and what narrative style is used. When violent themes appear in book-promotional posts, audiences more often adopt an oppositional stance, expressing disapproval or discomfort. In contrast, the same themes packaged as fantasy or POV-style content are more likely to be accepted, generating dominant-hegemonic reactions. Among the 15 analyzed comments, eight reflect oppositional positions, five are dominant-hegemonic, and two are negotiated. Interestingly, oppositional comments received the highest number of likes, suggesting that a silent majority may support these critical views even if they are not the loudest voices. Overall, this study highlights that TikTok users are not passive content consumers but active meaning-makers whose responses are shaped by context and content framing. It is recommended that future research expand this topic by incorporating audio elements, conducting interviews with audiences and creators, or exploring similar phenomena on other new media platforms to gain a deeper and more comprehensive understanding.